2021
DOI: 10.1111/are.15123
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic properties of Debaryomyces hansenii BCS004 and their immunostimulatory effect in supplemented diets for gilthead seabream ( Sparus aurata )

Abstract: Debaryomyces hansenii BCS004 strain is a non‐pathogenic, polyamine and superoxide dismutase secreting marine yeast. The objective of this study was to investigate the marine yeast DhBCS004 as probiotics and evaluate its antimicrobial properties and dietary immunostimulant effect on gilthead seabream specimens when administered at 106 colony‐forming unit/g−1 or 1.1% for 4 weeks. This yeast strain showed potential probiotic properties, including stability in gastrointestinal survival (pH, bile conditions) and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…While the liver was more sensitive to the PAP diet, the distal intestine was more sensitive to the PAP+YE diet. These results are consistent with an increase in expression of intestinal complement C3 in response to the use of yeast in gilthead seabream (84,85) . In fish fed the diet PAP+YE, the transcriptomic response of the intestine also revealed the modulation of genes related to mechanisms of pathogen control or allergic reaction.…”
Section: Discussionsupporting
confidence: 86%
“…While the liver was more sensitive to the PAP diet, the distal intestine was more sensitive to the PAP+YE diet. These results are consistent with an increase in expression of intestinal complement C3 in response to the use of yeast in gilthead seabream (84,85) . In fish fed the diet PAP+YE, the transcriptomic response of the intestine also revealed the modulation of genes related to mechanisms of pathogen control or allergic reaction.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the identified yeasts were tolerant to bile salts (0.6%–1.5%). Similarly, yeast strains Sporidiobolus ruineniae A45.2, D. hansenii BCS004, Kluyveromyces lactis M3, and Pichia kudriavzevii ONF7.1C have been reported to be tolerant to bile salts (Ghosh et al, 2017; Kanpiengjai et al, 2020; Reyes‐Becerril et al, 2021). Furthermore, the yeast strains jpn01, jpn02, jpn05, and jpn06 isolated from the gut of goldfish grew well and tolerated low pH and bile salt concentrations (Taha et al, 2023).…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…In addition, Kanpiengjai et al (2020) reported that Sporidiobolus ruineniae A45.2 was tolerant to pH 2 (Kanpiengjai et al, 2020). It has been noted that the yeast strain D. hansenii BCS004 isolated from surface seawater can also survive under low pH conditions (Reyes-Becerril et al, 2021).…”
Section: _ Is Cu S S _ Io Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance to salt, acid pH, and bile salts Antimicrobial activity against pathogenic bacteria in aquaculture (Aeromonas hydrophila, Vibrio vulnificus, Vibrio parahaemolyticus, and Photobacterium damselae) Improvement in the immune response through effect on leucocyte phagocytic capacity, respiratory burst activity, peroxidase activity, serum C3 and IgM levels, and regulation of cytokine gene expression [89] Mouse intestine Mice Increase in the operational taxonomic units of intestinal bacteria Promotion of the growth of beneficial intestinal bacteria [90,91]…”
Section: Human Dendritic Cells Micementioning
confidence: 99%